Aplikasi Teori Belajar Bruner Pada Pembelajaran Matematika - Khai Runnisa; Apria Rahmadhani; Nisrina Ath Thahirah; Wulan Agustin; Nazaha Rama Khairani; Dini Palupi Putri (IBTIDAIYAH: Jurnal Penelitian dan Pendidikan Dasar Islam, 2026)
Education is an important part of human life that aims to improve quality of life through the development of knowledge, skills, and abilities. In the learning process, teachers play a key role in determining strategies, methods, and techniques to ensure effective learning. However, many teachers still use traditional and monotonous teaching methods, causing students to become less active, less motivated, and have difficulty understanding mathematical concepts that are abstract, deductive, and symbolic. Therefore, innovative teaching strategies are needed to encourage active participation and develop students’ critical thinking skills. One approach is Jerome S. Bruner’s learning theory, which uses enactive, iconic, and symbolic representations to support discovery learning. This approach helps students understand concepts gradually, from concrete to abstract ideas. This study uses a qualitative literature review method by examining journal articles and relevant books. The findings show that applying Bruner’s theory in mathematics education can increase learning motivation, conceptual understanding, critical thinking skills, and systematic problem-solving abilities.